Resistance to checkpoint blockade therapy through inactivation of antigen presentation. Issue 1 (December 2017) - Sade-Feldman, Moshe; Jiao, Yunxin; Chen, Jonathan; Rooney, Michael; Barzily-Rokni, Michal; Eliane, Jean-Pierre; Bjorgaard, Stacey; Hammond, Marc; Vitzthum, Hans; Blackmon, Shauna; Frederick, Dennie; Hazar-Rethinam, Mehlika; et al.
Abstract Treatment with immune checkpoint blockade (CPB) therapies often leads to prolonged responses in patients with metastatic melanoma, but the common mechanisms of primary and acquired resistance to these agents remain incompletely characterized and have yet to be validated in large cohorts. By analyzing longitudinal tumor biopsies from 17 metastatic melanoma patients treated with CPB therapies, we observed point mutations, deletions or loss of heterozygosity (LOH) in beta-2-microglobulin (B2M ), an essential component of MHC class I antigen presentation, in 29.4% of patients with progressing disease. In two independent cohorts of melanoma patients treated with anti-CTLA4 and anti-PD1, respectively, we find thatB2M LOH is enriched threefold in non-responders (~30%) compared to responders (~10%) and associated with poorer overall survival. Loss of both copies ofB2M is found only in non-responders.B2M loss is likely a common mechanism of resistance to therapies targeting CTLA4 or PD1. Resistance to immune-checkpoint blockade often occurs in treated patients. Here, the authors demonstrate thatB2M loss is a mechanism of primary and acquired resistance to therapies targeting CTLA4 or PD-1 in melanoma patients.